2017
DOI: 10.4236/jep.2017.83021
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Cassava Peel for Treatment of Mine Water in Mozambique

Abstract: In the last decade, Mozambique became one of the top coal producers in Africa. The coal mines are in Moatize district in the center of the country, inside the lower Zambezi river basin. Pollution due to mining activities has negative impacts in agriculture, fishing, water supply, and presents risks to public health. Mozambique is one of the largest cassava producers in the world. More than 1.5 million tons of cassava peel are generated in the country and this agrowaste is discarded. The aim of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Starch has been recognised as the most extensively studied coagulant aid due to its biodegradability and susceptibility to modi cation [42]. Various past reviews and studies have reported the potential of tapioca peel in water and wastewater remediation [36,40,43,44,45,46]. The application of tapioca peel is mostly made in the form of activated carbon, which is also known as a cheap bio-adsorbent in the engineering discipline.…”
Section: Potential Of Tapioca Peel Powder (Tpp) As a Natural-based Comentioning
confidence: 99%
See 3 more Smart Citations
“…Starch has been recognised as the most extensively studied coagulant aid due to its biodegradability and susceptibility to modi cation [42]. Various past reviews and studies have reported the potential of tapioca peel in water and wastewater remediation [36,40,43,44,45,46]. The application of tapioca peel is mostly made in the form of activated carbon, which is also known as a cheap bio-adsorbent in the engineering discipline.…”
Section: Potential Of Tapioca Peel Powder (Tpp) As a Natural-based Comentioning
confidence: 99%
“…The conversion of this agro-waste into activated carbon is acknowledged to extend its lifespan. The peel is chemically modi ed using the respective concentration of acids to stimulate the particular cell wall and surface [43]. The bio-adsorbent has been widely used for sequestering heavy metal ions [32,36,40], mine water treatment [43], gas puri cation, and uid detoxi cation [45].…”
Section: Potential Of Tapioca Peel Powder (Tpp) As a Natural-based Comentioning
confidence: 99%
See 2 more Smart Citations
“…The plants such as Moringa oleifera and rice starch can be locally grown, where there is a lot of land space available (Rasool et al 2016;Teixeira et al 2017). The thoughts in commercialization of natural materials as coagulants might also boost the social factor of the locals that rely on these agricultural economy (Pondja et al 2017;Yin 2010), also probably as solution towards wastewater and agro waste pollution. The renewable sources of them also mean the continuous supply of raw materials in development of coagulants.…”
Section: Future Potential and Constraint Of Natural Materials As Commmentioning
confidence: 99%